Providing freedom or financial remuneration? A cross-sectional study on the role of monetary and legal incentives on COVID-19 further booster vaccination intention in the Italian context - Barello, Serena; Acampora, Marta; Paleologo, Michele; Palamenghi, Lorenzo; Graffigna, Guendalina (Frontiers in Public Health, 2023)
Vaccine hesitancy became a more and more important issue during the Covid-19 pandemic. Due to the emergence of new variants, many international health agencies have already begun administering booster doses of the vaccine in response to these threats. Studies have emphasized the effectiveness of different types of incentive-based strategies to increase vaccination behaviors. The purpose of the present study was to identify the correlation between different types of incentives (legal or financial) with people’s intentions to get a Covid-19 booster vaccine. We conducted a cross-sectional study between 29 January 2022 and 03 February 2022. An online quantitative survey was carried out in Italy. One thousand and twenty-two Italian adults were recruited by a professional panel provider. Descriptive statistics were computed for the five variables concerning the incentives toward vaccination. A general linear model (GLM) was then computed to compare the scores of the five different variables within the subjects. The General Linear Model showed a significant within-subjects main effect. Post-hoc comparisons showed that among the financial incentive, the monetary reward is rated lower than all the others. Tax and Fees both resulted lower than both the legal incentives. Finally, Covid-19 health certification and Travel did not result significantly different from each other. This study offers an important contribution to public policy literature and to policymakers in their efforts to explain and steer booster vaccination acceptance while facing an ongoing pandemic.